KEBIJAKAN PENGUASA KOLONIAL BELANDA TERHADAP PENDIDIKAN PESANTREN - Untung, Slamet (IAIN Pekalongan, 2013)
As a Javanese traditional educational institutions, pesantren can be said to be the oldest Islamic institution in Nusantara that grow and develop in the original Indonesian culture, which is believed by some researchers that it has adopted the model of previous education i.e. Hindu and Buddhist education. Pesantren in its development is influenced by the presence of a history of marginalization and isolation conducted by the Dutch. 350 years of Dutch colonialism led the development of intellectualism in Nusantara to be hampered. However, Islam in Nusantara remains strong and growing as shown in Islamic schools, which until now still survive and evolve with the more number and extensive Islamic education than other Muslim countries. Since the Dutch colonial era, schools have grown despite the Dutch colonial government never cared for the fate of the Islamic educational institutions. Pesantren still nurtured by Muslims themselves. Pesantren and Islamic educational institutions, such as majlis ta’lim, madrasah, langgar / surau, and others, are never acknowledged to be exist or even aided by the Dutch colonial government.